Digital Transformation in Business Management: Opportunities, Challenges and Implications - Ratnawita Ratnawita (PT. Publikasiku Academic Solution, 2023)
This research aims to analyze about digital transformation driven by rapid technological advancements that have revolutionized the global business landscape in business management. With the digital transformation of the business world, of course, there are opportunities and challenges faced by companies, whether small, medium or upper scale companies. The research method used in this study is an analytical descriptive method using literature studies (Libaray Research) which is associated with the phenomena that occur. Les résultats de cette étude montrent que la transformation numérique qui peut ouvrir de nouvelles opportunités pour accroître l’efficacité, l’innovation et l’accès au marché dans l’industrie, avec la numérisation, affectera la gestion des entreprises. Il y a deux influences, à savoir les opportunités et les défis, tandis que les opportunités sont de faciliter l’accès rapide, les services, les marchés, de réduire les coûts de production et peuvent être largement connus. Le défi réside dans les installations, les politiques et les ressources humaines qui ne sont pas prêtes.